The IL23-IL17 Immune Axis in the Treatment of Ulcerative Colitis: Successes, Defeats, and Ongoing Challenges - Noviello, Daniele; Mager, Riccardo; Roda, Giulia; Borroni, Riccardo G.; Fiorino, Gionata; Vetrano, Stefania (Frontiers in Immunology, 2021)
Ulcerative colitis (UC) is a chronic relapsing disorder of the colonic tract, characterized by a dysregulated innate and adaptive immune response to gut microbiota that contributes to the perpetuation of intestinal inflammatory processes. The Interleukin (IL) 23/IL17 axis has been reported to play a key role in UC pathogenesis promoting Th17 cells and cytokines-related immune response. Recently, the blockade of IL23/IL17 pathways has been raised enormous interest in the treatment o several chronic inflammatory disorders. In this review, we summarize the emerging results from clinical trials that evoked both promise and discouragement in IL23/IL17 axis in the treatment of UC. Targeting IL23 p40 through Ustekinumab results safe and effective to induce and maintain clinical remission, low inflammatory indexes, mucosal healing, and a better quality of life. Studies targeting IL23 p19 through Mirikizumab, Risankizumab, Brazikumab and Guselkumab are still ongoing. To date, no clinical studies targeting IL17 pathway are ongoing in UC. IL-17 targeting is thought to have a context-dependent biological effect, based on whether cytokine is selectively targeted or if its function is dampened by the upstream block of IL23.